Synthesis, Characterization and Antimicrobial Activity of Three Gallates Containing Imidazole, Benzimidazole and Triclosan Units - Wang1, Zhiyuan; Gu1, Haibin; Chen1, Wuyong (Asian Journal of Chemistry, 2014)
Three new gallates containing the antimicrobial units of imidazole, benzimidazole and triclosan, respectively, were designed and synthesized. Firstly, the direct esterification method, in which p-toluenesulfonic acid was used as the catalyst, was adopted to synthesize the three gallates. Results show that it is infeasible to obtain the target products, especially for the direct esterification reaction of 5-methyl-2-nitro-imidazole-1-ethanol and gallic acid, the synthesized product is just a complex composed by equimolar 5-methyl-2-nitro-imidazole-1-ethanol and gallic acid and stabilized by a lot of intramolecular and intermolecular hydrogen bonds, which was proved by the single-crystal X-ray diffraction analysis. Another, the indirect esterification method, in which the phenolic hydroxyl groups of gallic acid were first protected by acetyls as shown in Scheme-I, was employed. The obtained compounds were proved to be the expected products by elemental analysis, IR, 1H NMR, 13C NMR and X-ray single-crystal diffraction. Finally, the inhibition zone method was used to determine the antimicrobial effect of the synthesized gallates and their initial compounds. Results indicate that the introduction of the three antimicrobial units has obvious synergistic or additive effect on the antimicrobial activities of gallates. The gallates shows different inhibitory effect against different tested microbes, which is mainly decided by the introduced antimicrobial units.